THE DEVELOPMENT OF WEB-BASED LEARNING MULTIMEDIA FOR HIGH SCHOOL STUDENTS’ LITHOSPHERE MATERIAL - Ellese Sulistianingsih; M Mukminan (Department of Geography Education, University of Jember, 2019)
Science and Technology develop very fast in every aspect of life, including in the aspect of education. As the development of science and technology, guiding teachers to be able to make use various kinds of creative and innovative learning media in learning process at school is needed in order to increase the effectivity of the learning process which will have impact on the students’ learning motivation and learning outcomes. According to the explanation, learning multimedia needs to be developed in order to increase the students’ learning motivation and learning outcomes. This research is a research and development (R&D), which is then modified by using Tessmer formative evaluation. The analysis results show that the web-based learning multimedia for lithosphere material has been proven its eligibility, that the web-based learning is valid, practical, to be used in learning process and is effective in increasing students learning motivation and learning outcomes. References Bowman, S. F. (2015). Evaluation in Instructional Design Practice: A View from The Stakeholders. (Dissertation Doctor, Capella University, 2015). Retrieved from https://search. proquest.com/docview/1707694509/fulltext PDF/D439E6E103D04792PQ/6?accountid=31324. Cahyono, K. (2013). Penggunaan Media Interaktif Berbasis Web untuk Meningkatkan Motivasi dan hasil Belajar. Jurnal Teknik Informatika Abdurrab University. Retrieved from http://binaprajajournal.com/ojs/index. php/jbp/article/view/117. Daljoeni, N. (2014). Pengantar Geografi. Yogyakarta: Ombak. Day, T. (2012). Undergraduate Teaching and Learning in Physical Geography. Journal Physical Geography, 36(3). Retrieved fom https://search. proquest. com/doc view/1019246195/B5C4C63F0A8F4962PQ/1?accountid=31324. Fadli, M. S. & Ikawati, H. D. (2017). Penggunaan Multimedia untuk Meningkatkan Motivasi Belajar Siswa. Jurnal Teknologi Pendidikan, 2(2). Retrieved from http://ojs.ikipmataram.ac.id/index.php/jtp/article/view/598. Gilakjani, A. P. (2012). The Significant Role of Multimedia in Motivating EFL Learners’ Interest in English Language Learning. Journal Modern Education and Computer Science, 4(4). Retrieved from https://search. proquest.com/docview/1627735482/509798BC9EC481FPQ/1?accountid=31324. Hake, R. R. (1999). Analyzing Change/Gain Score. Dept. of Physics, Indiana University. Retrieved from http://www.physics.indiana.edu/ sdi/Analyzing Change-Gain. Hawley, D & Lyon, J. (2017). Plate Update: Refreshing Ideas for Teaching Plate Tectonics. Teaching Geography, 42(1). Retrieved from https://search.pro quest.com/docview/1952375936/73816528324E4DACPQ/1?accountid=31324. Huang, Q. (2012). Action Research on Motivation in English Reading. Journal Theory and Practice in Language Studies, 2(8). Retrieved from https://search. proquest.com/docview/1619300790/fulltextPDF/D04EC91FA9214B89PQ/2?accountid=31324. Kusumaningtias, A. D. & Mukminan. (2014). Pengembangan Multimedia Pembelajaran Geografi dengan Materi Litosfer dan Pedosfer untuk SMA Kelas X. Jurnal Ilmu-ilmu Sosial, 11(1). Retrieved from https://jurnal.uny.ac.id/index.php/sosia/article/download/5284/4583. Milovanovic, M. Perisic, J., Vukotic, S. Bugarcic, M. Radovanovic, L. &Ristic, M. (2016). Learning Mathematic Using Multimedia in Engineering Education. Journal Acta Technica Corviniensis – Bulleting of Engineering, 9(1). Retrieved from https://search.proquest.com/docview/1767584934/559B63 F69E094F98PQ/1?accountid=31324. Moeed, A. (2015). Science Investigation Students View about Learning, Motivation and Assessment. Singapore: Springer. Mohasin, S. F., Shinde, P. A. &Khaparde. (2013). E-Learning: A Tool for Library and Information Services. Journal of Library & Information Science, 3(2). Retrieved from https://search.proquest.com/docview/1440877148/fulltext PDF/33223E6022A248ECPQ/1?accountid=31324. Permadi, A. A. (2016). Pengembangan Media Pembelajaran Interaktif Berbasis Web dengan Pemanfaatan Video Conference Mata Pelajaran Produktif Teknik Komputer dan jaringan di Sekolah Menengah Kejuruan. Jurnal Pendidikan Teknologi dan Kejuruan. Retrieved from http://jural.unm.ac.id/ 3123/1/Jurnal.pdf. Presiden Republik Indonesia. (2000). Keputusan Presiden Republik Indonesia Nomor 50 Tahun 2000 Tentang Tim Koordinasi Telematika Indonesia. Robb, C. (2010). The Impact of Motivational Messages on Student Performance in Community College Online Courses. (Dissertation Doctor, University of Illinois at Urbana-Champaign, 2010). Retrieved from https://search.proquest.com/docview/778224030/18ED422A32FC4231PQ/3?accountid=31324 Sahrir, M. S., Alias, N. A., Ismail, Z., & Osman, N. (2012). Employing Design and Development Research (DDR): Approaches in the Design and Development of Online Arabic Vocabulary Learning Games Prototype. Journal of Educational Technology, 11(2). Retrieved from https://search. proquest.com/docview/1288340626/fulltextPDF/D439E6E103D04792PQ/1?accountid=31324. Sari, H. V. & Suswanto, H. (2017). Pengembangan media pembelajaran Berbasis Web Untuk mengukur hasil Belajar siswa pada mata pelajaran Komputer Jaringan Dasar program Keahlian teknik komputer dan jaringan.Jurnal Pendidikan, 2(7). Retrieved from http://journal.um.ac.id/index.php/jptpp/ article/view/9734/4593. Su, C. H. (2016). The effects of students' motivation, cognitive load and learning anxiety in gamification software engineering education: a structural equation modeling study. Journal Multimedia Tools Application, 75(16). Retrieved from https://search.proquest.com/docview/1867930658/fulltextPDF/9482B 31FA03D4E7CPQ/1?accountid=31324. Tessmer, M. (1998). Planning and Conducting Formative Evaluation. London: Kogan Page Limited. Tsai, M. J. (2009). The Model of Strategic e-Learning: Understanding and Evaluating Student E-Learning from Metacognitive Perspectives. Journal Educational Technology & Society, 12(1). Retrieved from https://search. p1roquest.com/docview/1287039259/20B52566A67140DBPQ/1?accountid=31324. Umar. (2013). Studi Komparatif Penguasaan Konsep Ulumul Qur’an Dalam Pembelajaran Yang Menggunakan Full E-Learning Dan Blended E-Learning. Jurnal TAPIS, 13(1). Retrieved from http://id.portalgaruda.org/? ref=browse&mod=viewarticle&article=252276. Wiyani, N. A. (2012). Desain Pembelajaran Pendidikan: Tata Rancang Pembelajaran Menuju Pencapaian Kompetensi. Yogyakarta: Ar-Ruzz Media. Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License